2006
DOI: 10.1073/pnas.0601436103
|View full text |Cite
|
Sign up to set email alerts
|

Bone-marrow-derived stem cells repair basement membrane collagen defects and reverse genetic kidney disease

Abstract: Type IV collagen is a predominant component of basement membranes, and glomeruli of a kidney filter Ϸ70 -90 liters of plasma every day through a specialized glomerular basement membrane (GBM). In Alport syndrome, a progressive disease primarily affecting kidneys, mutations in GBM-associated type IV collagen genes (COL4A3, COL4A4, or COL4A5) lead to basement membrane structural defects, proteinuria, renal failure, and an absence of all three GBM collagen triple helical chains because of obligatory posttranslati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
174
5
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 228 publications
(188 citation statements)
references
References 28 publications
(28 reference statements)
3
174
5
5
Order By: Relevance
“…Two recent article reported evidence for the GBM expression of type IV collagen ␣3 chains and improved renal function after wild-type BMT to the Col4a3-deficient AS mice 10,11 ; however, Sugimoto et al 10 did not present any data of KO to KO BMT mice, and those of Prodromidi et al 11 were also limited (the study group was composed of three mice). Those studies differ from this one in regard to the time of transplantation and the strain.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Two recent article reported evidence for the GBM expression of type IV collagen ␣3 chains and improved renal function after wild-type BMT to the Col4a3-deficient AS mice 10,11 ; however, Sugimoto et al 10 did not present any data of KO to KO BMT mice, and those of Prodromidi et al 11 were also limited (the study group was composed of three mice). Those studies differ from this one in regard to the time of transplantation and the strain.…”
Section: Discussionmentioning
confidence: 78%
“…10,11 Both groups showed some improvement in renal injury on the basis of the laboratory data and histology; however, so far, no report has addressed the survival time of these mice, which is essential to judge the effectiveness of bone marrow transplantation (BMT). 12 Therefore, the short-term and long-term effects on BMT were analyzed in our study using larger sample sizes.…”
mentioning
confidence: 99%
“…Nevertheless, BM transplantation can improve renal function. Whole BM transplantation has been reported to be able to improve renal function and reduce histological damage in the collagen4α3 defective model of Alport syndrome [24,25]. These authors reported that BM-derived cells transdifferentiated into podocytes and mesangial cells, accompanied by re-expression of the defective collagen chains and improved renal histology and function.…”
Section: Bone Marrow-derived Cellsmentioning
confidence: 99%
“…Furthermore, ex vivo manipulation of macrophages using specific cytokines confirmed that classically activated, M1 macrophages worsen chronic inflammatory adriamycin nephropathy, whereas alternatively activated M2 macrophages reduce histological disruption and functional injury [36]. Of note, in the heart Camargo et al [37] have [39] Glycerol-induced ARF (mouse) MSCs Enhanced tubular proliferation [68] IR (rat) Papilla LRCs Proliferation and incorporation [149] IR (mouse) Bone marrow No functional improvement, intrarenal cells are the main source of repopulating cell during repair [22] Folic acid-induced acute tubular injury (mouse) Bone marrow Intrinsic tubular cell proliferation accounts for repair after damage [150] Folic acid-induced acute tubular injury (mouse) Bone marrow 10% incorporation in tubules and G-CSF doubles this rate [151] IR (rat) MSCs Improved renal function and less injury [152] Cisplatin-induced renal failure (mouse) MSCs Accelerated tubular proliferation [153] UUO (mouse) Bone marrow macrophages Reduced renal fibrosis [41] IR (rat) MSCs Improved renal function, increased proliferation and decreased apoptosis [84] IR (rat) rKS56 (S3 segment outgrowth) Replace tubular and improve function [80] Glycerol-induced tubulonecrosis (mouse) Human CD133 + cells Homing and tubular integration [66] UUO (rat) Label-retaining cells (LRC) Proliferates, migrates and transdifferentiates into fibroblast-like cells [27] Cisplatin-induced renal failure (mouse) G-CSF ± M-CSF Improvement in renal function and prevention of renal tubular injury [154] Anti-Thy1.1 GN (rat) MSCs Increased glomerular proliferation and reduction in proteinuria [53] Col4α3 deficiency (mouse) MSCs Prevented loss of peritubular capillaries and reduced fibrosis but no increase in function or survival [24] Col4α3 deficiency (mouse) Bone marrow Partial restoration of expression of the type IV collagen α3 chain, improved histology and function [25] Col4α3 deficiency (mouse) MSCs Improved function and glomerular scarring and interstitial fibrosis reduced [155] UUO (mouse) BM Instertitial BM-derived cells do not contribute significantly to collagen synthesis after damage [74] Adriamycin-nephropathy (mouse) Renal side population Functional amprovement but very low rate of engraftment. [78] IR (rat) Multipotent renal progenitor cells In vivo epithelial differentiation, no difference on renal function [67] Cultured met...…”
Section: Bone Marrow-derived Cellsmentioning
confidence: 99%
See 1 more Smart Citation